Luật lệ cưa nước Việt-Nam dân chủ cộng hòa (Vietnamese law coll. (Harvard Law School), 1962)
Abstracts of important laws and regulations arranged in 5 categories: administrative law, financial law, civil law, labor law, and criminal law.